Microbicides and their potential as a catalyst for multipurpose sexual and reproductive health technologies. (October 2014) - Abdool Karim, Q; Baxter, C; Abdool Karim, S
Abstract : There is an urgent need for technologies to prevent sexual acquisition of HIV infection in young women in sub‐Saharan Africa. After two decades of 11 pivotal trials of seven products, anti‐retroviral‐based topical microbicides are showing promise. Building on the CAPRISA 004 trial findings, several trials of new anti‐viral agents, novel delivery mechanisms and combination/multipurpose products that address challenges of adherence and meet the sexual and reproductive health needs of men and women, including preventing HIV infection, are underway.